Teletrabalho na Administração Pública: evidências do processo de implantação e fatores de adesão ao Programa de Gestão e Desempenho (PGD) no Instituto Federal Goiano - Pena, Kenny William (2024)
This work's main objective is to evaluate the main characteristics of the technical-administrative employees in education (TAE) who decisively influenced adherence to the Management and Performance Program (PGD) at the Federal Institute Goiano (IF Goiano). PGD is a management program that encourages the development of employees and replaces frequency control with productivity control, with defined goals, deadlines and tasks, focusing on delivering results and the quality of services provided to society. The research problem of this work focused on identifying the main characteristics and factors that influenced adherence to the PGD, specifically among administrative technicians. The methodology used was a descriptive research with a mixed approach, combining quantitative methods, through questionnaires applied to administrative technicians, and qualitative methods, making an analysis of the perspective and point of view of the TAEs of IF Goiano who joined the PGD. Data collection and collection took place through a survey questionnaire with open and closed questions, structured to collect data on individual characteristics, characteristics of activities, functional positions and the work environment, characterization of adherence to the PGD and perception of TAEs after joining the PGD, reporting this professional experience, the expectations and motivations of the participants. The information collected received descriptive and econometric statistical treatment based on the probit regression model, which estimates the probability of an event occurring, assuming that the dependent variable follows a standard normal distribution. The results extracted from the descriptive statistical analysis showed that the vast majority of TAEs interviewed and who joined the PGD (96.9%) had an easy adaptation; 93.9% of those who joined the PGD said they were satisfied with the program, and more than 90% agreed that maintaining the PGD is beneficial. The estimated econometric results, in general, showed that being female, married, not having children and having, at the same time, adequate physical structure and technological skills (computational, information and communication) are significant and important characteristics for the decision of TAE employees whether or not to join the PGD. Finally, an institutional intervention proposal was created, with the aim of assisting IF Goiano in improving the program, adjusting it according to the needs and expectations of employees and the institution, as well as serving as a basis for future studies related to PGD.